Cowpea-structured PVDF/ZnO nanofibers based flexible self-powered piezoelectric bending motion sensor towards remote control of gestures. (January 2019) - Deng, Weili; Yang, Tao; Jin, Long; Yan, Cheng; Huang, Haichao; Chu, Xiang; Wang, Zixing; Xiong, Da; Tian, Guo; Gao, Yuyu; Zhang, Haitao; Yang, Weiqing
Abstract: Interactive human-machine interface (iHMI) is a bridge connecting human beings and robots, which has an important requirement for perceiving the change of pressure and bending angle. Here, we designed a flexible self-powered piezoelectric sensor (PES) based on the cowpea-structured PVDF/ZnO nanofibers (CPZNs) for remote control of gestures in human-machine interactive system. Due to the synergistic piezoelectric effect of hybrid PVDF/ZnO and the flexibility of polymer, this PES exhibited excellent bending sensitivity of 4.4 mV deg −1 ranging widely from 44° to 122°, fast response time of 76 ms, and good mechanical stability. Besides, the PES could operate under both bending and pressing mode, show ultrahigh pressing sensitivity of 0.33 V kPa −1, with response time of 16 ms. When integrated in iHMI, the PES could be conformably covered on different curve surfaces, demonstrated accurate bending angle recording and fast recognition for realizing intelligent human-machine interaction. On this basis, the application of remote control of robotic hand was successfully realized in form of acting the same gesture as human hand synchronously. This CPZNs-based self-powered PES is distinct and unique in its structure and fundamental mechanism, and exhibits a prospective potential application in iHMI. Graphical abstract: fx1 Highlights: A novel cowpea-structured PVDF/ZnO nanofiber has been designed. The fabricated sensor exhibited excellent performance under bending and pressing mode. Excellent flexibility and conformability accommodating to skin were obtained. Remote control of gestures were successfully realized based on the fabricated sensor.